Polyurethane, method for preparing polyurethane and coating
By using hydrophobically modified isocyanate and anti-UV nanofillers in polyurethane, combined with the modification technology of aspartate sterically hindered secondary ammonia, the anti-photoaging and self-cleaning performance of polyurethane is improved, and the insufficient performance of traditional polyurethane is solved. The problem of high efficiency of coating solid content and environmental protection.
Patent Information
- Application Number
- CN202310866338.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
AI Technical Summary
Traditional polyurethanes have shortcomings in their anti-photoaging and self-cleaning properties, resulting in the need of additional composite waterproof coatings for improved performance, but this increases the construction complexity and risk of interlayer delamination.
Using hydrophobic modified isocyanate and anti-UV nanofiller, polyurethane is formed by grafting modification of low surface energy components of aspartate sterically hindered secondary ammonia, which improves its anti-photoaging and self-cleaning properties, and through Appropriate viscosity and surface energy, reduce solvent usage, and improve solid content and environmental protection.
It achieves high weather resistance, self-cleaning effect and sunlight reflectivity of polyurethane, which is suitable for outdoor applications, reduces the surface temperature of the coating and improves the energy-saving performance of the building.
Smart Images

Figure BDA0004339400330000021 
Figure BDA0004339400330000041 
Figure BDA0004339400330000081
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of materials, and in particular to polyurethane, a method for preparing polyurethane, and coatings. Background Art
[0002] Polyurethane is widely used in fields such as construction, automotive, and aviation, for example, in the formation of waterproof coatings. One-component polyurethane waterproof coatings are made by mixing and processing an isocyanate-containing prepolymer formed through the addition polymerization of isocyanates and polyether polyols, along with a catalyst, anhydrous additives, anhydrous fillers, and solvents. These are based on polyurethane prepolymers and are free of additives such as tar and asphalt. These coatings are reaction-curing (moisture-curing) coatings characterized by high strength, high elongation, excellent water resistance, and strong adaptability to substrate deformation.
[0003] However, current polyurethanes, methods for preparing polyurethanes, and coatings. Summary of the Invention
[0004] The present disclosure aims to provide a polyurethane, a method for preparing the polyurethane, and a coating to solve or alleviate one or more technical problems in the related art.
[0005] As a first aspect of an embodiment of the present disclosure, the present disclosure provides a polyurethane. The raw materials for forming the polyurethane include:
[0006] UV-resistant nanofillers;
[0007] Hydrophobically modified isocyanates;
[0008] Polyether polyols;
[0009] Latent amines; and
[0010] additive,
[0011] The hydrophobically modified isocyanate is formed by grafting and modifying a low surface energy component in the presence of aspartic acid ester sterically hindered secondary amine.
[0012] In some examples, the polyurethane has a viscosity of 6000-9000 mPa·s.
[0013] In some examples, the UV-resistant nanofiller and the latent amine are modified with the aspartic acid ester-based sterically hindered secondary amine.
[0014] In some examples, the aspartic acid ester-type hindered secondary amine is a compound represented by Formula I:
[0015]
[0016] Wherein, R1-R4 are independently selected from C1-C8 alkyl groups.
[0017] In some examples, R1-R4 are each independently a C2-C8 linear alkyl group.
[0018] In some examples, the anti-UV nanofiller includes at least one of titanium dioxide, cerium oxide, zinc oxide, tungsten oxide, silicon oxide, and vanadium oxide.
[0019] The particle size of the anti-UV nanomaterial is 20-100 nm.
[0020] In some examples, the additive includes at least one of a dispersant, a defoaming agent, a filler, a plasticizer, and a accelerator.
[0021] In another aspect of the present disclosure, a method for preparing the aforementioned polyurethane is provided, comprising the steps of forming a hydrophobically modified isocyanate, mixing the hydrophobically modified isocyanate, a polyether polyol, and an additive for prepolymerization, and then adding a latent amine to obtain the polyurethane.
[0022] In some examples, forming the hydrophobically modified isocyanate includes: adding a solution containing an anti-UV nanofiller and a low surface energy component to the isocyanate, and stirring the reaction in an oil bath at 80-120 degrees Celsius, wherein the solution containing the anti-UV nanofiller contains aspartic acid ester-type hindered secondary amine.
[0023] In some examples, obtaining the solution containing the anti-UV nanofiller comprises the following steps: adding a solvent to the aspartic acid ester hindered secondary amine, wherein the anti-UV nanofiller is dispersed in the solvent, and heating and stirring the reaction for 12-24 hours.
[0024] In some examples, the latent amine is an internal plasticizing latent amine, and forming the internal plasticizing latent amine includes:
[0025] Adding aspartic acid ester type hindered secondary amine into a closed reactor and adding a solvent;
[0026] Add benzaldehyde dropwise under stirring, control the reaction temperature not higher than 80°C, and continue to keep the temperature for reaction after the addition is completed;
[0027] The reacted material is refluxed to remove water and subjected to reduced pressure distillation.
[0028] In another aspect of the present disclosure, a coating is provided, wherein the coating comprises polyurethane, and the polyurethane is as described above or prepared by the method described above.
[0029] In some examples, the coating satisfies at least one of the following conditions:
[0030] The solid content of the coating is not less than 80%;
[0031] The film layer formed by the coating has a water contact angle of not less than 120 degrees;
[0032] The artificial weathering time of the film formed by the coating is not less than 2000 hours;
[0033] The solar hemispherical reflectivity of the film layer formed by the coating is not less than 80%.
[0034] The polyurethane and preparation method proposed in the present disclosure, by using hydrophobically modified isocyanate and anti-UV nanofiller components, the obtained polyurethane and the coating based on the polyurethane have the advantages of being safe and environmentally friendly, having a moderate curing speed, having a large wetting ability for the base layer, strong adhesion, and having good bonding to a variety of substrates.
[0035] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present disclosure will be readily apparent from the following detailed description. DETAILED DESCRIPTION
[0036] In the following, only certain exemplary embodiments are briefly described. As will be appreciated by those skilled in the art, the described embodiments may be modified in various ways without departing from the spirit or scope of the present disclosure, and different embodiments may be combined in any manner without conflict. Therefore, the following description is to be regarded as illustrative in nature and not restrictive.
[0037] In its first aspect, the present disclosure provides a polyurethane. The raw materials for forming the polyurethane include a UV-resistant nanofiller, a hydrophobically modified isocyanate, a polyether polyol, a latent amine, and additives. The hydrophobically modified isocyanate is formed by grafting a low-surface-energy component in the presence of a sterically hindered secondary amine such as an aspartic acid ester.
[0038] The inventors have discovered that traditional polyurethanes, especially traditional single-component polyurethanes, have poor light aging resistance, insufficient durability, the need for additional protective layers on exposed parts, and insufficient surface self-cleaning ability. Therefore, due to the above-mentioned deficiencies in light aging resistance and self-cleaning ability, traditional polyurethanes generally adopt the method of requiring additional composite waterproof coatings to improve the corresponding performance. However, the addition of structures such as waterproof layers will lead to an increase in the number of construction passes on the one hand, and on the other hand, it also increases the risk of interlayer delamination. The present application improves the material's light aging resistance and alleviates the problems of organic aging and decomposition caused by light aging by adding specifically modified hydrophobically modified isocyanates and anti-UV nanofillers. On the other hand, the isocyanate formed by grafting and modifying low surface energy components in the presence of aspartic acid ester sterically hindered secondary amines provides a good cross-linked network structure foundation for the system, thereby obtaining appropriate viscosity and low surface energy, thereby improving the self-cleaning performance of the polyurethane and further preventing the occurrence of various aging. In addition, polyurethanes with appropriate viscosity have the advantages of reducing the amount of solvent used and increasing the solid content of the coating when forming a coating, which is green and environmentally friendly.
[0039] In some examples, the viscosity of the polyurethane is 6000-9000 mPa.s. Polyurethane with such viscosity can be used to prepare a coating, and a coating with a solid content of more than 80%, or even about 90%, can be obtained, thus having the advantage of being green and environmentally friendly.
[0040] In some examples, the type and composition of the UV-resistant nanofiller are not particularly limited, as long as they provide photoaging resistance. For example, in some examples, the UV-resistant nanofiller includes at least one of titanium dioxide, cerium oxide, zinc oxide, tungsten oxide, silicon oxide, and vanadium oxide. These particles exhibit excellent photoaging resistance and can reduce damage to organic materials caused by light of specific wavelengths through physical and chemical reactions. For example, these materials can have strong reflectivity for light in the 300-400 nm wavelength range. The resulting UV-resistant nanofiller can have a reflectivity of at least 50% for light in the 300-400 nm wavelength range, and for light around 340 nm, a reflectivity of at least 50%, or even at least 60% or 70%. In some examples, the UV-resistant nanofiller can contain nanoparticles of titanium oxide, tungsten oxide, cerium oxide, and vanadium oxide mixed in a mass ratio of 1:2:1:1. The particle size of these nanoparticles or UV-resistant nanofillers is also not particularly limited. For example, the particle size of the UV-resistant nanomaterial can be 20-100 nm. Specifically, it can be 30nm, 50nm, 70nm, 80nm, 90nm, 100nm, etc.
[0041] In some examples, the hydrophobically modified isocyanate can be formed by grafting a low surface energy component in the presence of a sterically hindered secondary amine of the aspartic acid ester type. Specifically, aliphatic isocyanates can be selected for modification, such as one or two of Wanhua Chemical's IPDI, HDI, and HMDI. The low-energy surface component can include a fluorine-containing small molecule material. For example, it can be a fluorosilane, specifically one or two of tridecafluorooctyltriethoxysilane, heptafluorodecyltrimethoxysilane, pentafluorophenyltriethoxysilane, and nonafluorohexyltriethoxysilane. The above-mentioned fluorosilanes have low surface energy and moderate molecular weight, and the grafted polymer formed can provide good hydrophobicity to the polyurethane to achieve a self-cleaning effect. At the same time, the low surface energy substance of the small molecule can also avoid the poor hydrophobicity durability caused by aging and detachment. The presence of the sterically hindered secondary amine of the aspartic acid ester type can regulate the speed of grafting of the fluorosilane and the isocyanate, which is conducive to forming a good network structure and obtaining a polyurethane with a viscosity suitable for preparing coatings.
[0042] In some examples, the aspartic acid ester-type hindered secondary amine is a compound represented by Formula I:
[0043]
[0044] Wherein, R1-R4 are independently selected from C1-C8 alkyl groups.
[0045] In some examples, R1-R4 are each independently a C2-C8 straight-chain alkyl group. The inventors have found that the amino group of the sterically hindered secondary amine having the above structure has suitable steric hindrance, so that the chain extension and cross-linking reaction rate when forming polyurethane can be controlled, thereby obtaining a polyurethane with a uniform network structure and moderate viscosity. In some preferred examples, the above R1-R4 can be selected to contain a saturated straight-chain alkyl group of 8 carbon atoms or less, that is, R1-R4 does not contain an unsaturated bond, and includes but is not limited to heteroatoms such as O, S, N, and P. As a result, the chemical stability of the sterically hindered secondary amine is good, and side reactions are not likely to occur during the reaction, which is conducive to further improving the performance of the polyurethane. In addition, the R1-R4 carbon chain of moderate length can provide appropriate steric hindrance, thereby forming a more uniform graft network structure. On the one hand, the uniform graft network structure can provide a viscosity suitable for preparing coatings, and on the other hand, it can also improve the mechanical properties and weather resistance of the polyurethane.
[0046] In some preferred embodiments, the UV-resistant nanofillers and latent amines may also be modified with the aspartic acid ester-type hindered secondary amino groups.
[0047] Specifically, a solvent and the aforementioned aspartic acid ester hindered secondary amine can be added when forming the anti-UV nanofiller. The aspartic acid ester hindered secondary amine has multiple carboxyl groups and amino groups, which can undergo physical or even chemical reactions with the aforementioned nano-ions with the ability to reflect ultraviolet rays, including but not limited to adsorption. As a result, the aspartic acid ester hindered secondary amine in the anti-UV nanofiller can utilize the secondary amine to combine the nanoparticles with other components in a more tightly combined manner when forming polyurethane. Compared to ordinary mixing, the above process is conducive to better combining the effective nanoparticle components in the anti-UV nanofiller with the organic backbone of the polyurethane, which in turn helps to improve the weather resistance of the material and prevent the mechanically mixed filler from detaching from the organic backbone after a period of use, resulting in a decrease in light aging resistance.
[0048] In some preferred embodiments, a UV-resistant nanofiller modified with a sterically hindered secondary amine of an aspartic acid ester can be first formed and then added to an isocyanate to undergo a grafting reaction with a low-surface-energy small molecule. The inventors have discovered that the nanoparticles in the UV-resistant nanofiller also have a catalytic effect on this reaction, thereby accelerating the reaction.
[0049] In some examples, the latent amine may also be modified with a sterically hindered secondary amine from an aspartic acid ester. The hindered secondary amine having the structure shown in formula (I) above can provide good steric hindrance and thus control the reaction rate. As a result, the active groups in the plasticizing latent amine within the aspartic acid ester also have good reactivity. When R1-R4 in the structure shown in formula (I) above are independently C2-C8 linear alkyl groups, these segments can also provide a relatively rigid carbon chain, thereby improving the overall mechanical properties of the polyurethane and achieving relatively excellent weather resistance.
[0050] In some examples, the additives include at least one of a dispersant, a defoaming agent, a filler, a plasticizer, and a accelerator. Specifically, the dispersant may include one or more of the silane coupling agent WD50, f108 Hangzhou Lin'an auxiliary agent, KH550, KH560, and Deqian Chemical 9250 dispersant produced by Hubei Wuda Silicone Company; the defoaming agent may be at least one of the defoaming agent with brand number 066N produced by BYK Chemical Company, 5500 of Deqian Chemical, and the silicone defoaming agent of Shanghai Tiger Company; the filler may include ordinary fillers and weather-resistant fillers, and the ordinary filler may include Jiangsu Qunxin's heavy calcium 101a, 201a, Jiangxi Kete's talc powder 1000, Qingzhou Yuxin's calcium hydrogen 601, Suzhou Lida's heavy calcium ld200 and ld600, Guangyuan heavy calcium cc1500 and cc1000, and talc powder dhs218; the weather-resistant filler may include one or two of rutile titanium dioxide, barium sulfate, lithopone, silica fume powder, glass micropowder, and mica powder. The plasticizer can be selected from a combination of one or more of diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), chloropalm oil methyl ester, chlorinated paraffin, dioctyl adipate, glycol benzoate, trioctyl phosphate and alkyl phenyl sulfonate, and the accelerator can be selected from a combination of one or more of salicylic acid, benzoic acid and oleic acid.
[0051] Those skilled in the art will appreciate that the raw materials for forming polyurethane may also include solvents, amine catalysts, and other components. Amine catalysts may include pentamethyldipropylenetriamine, tetramethylethylenediamine, 1,8-diazacyclo[5,4,0]undecene, and BASF's bismorpholine organic amine catalysts. The solvent may be selected from tetramethylbenzene or trimethylbenzene, such as at least one of the aromatic solvents No. 150 and No. 100 from Hualun, Pengchen, or Wuyang Chemical.
[0052] The polyether polyol may be one or more of polyether polyol 2000D, polyether polyol 1000D, polyether polyol 400, polyether polyol N330 and polyether polyol 3050.
[0053] In the present disclosure, the content of the above components is not particularly limited, and those skilled in the art can select according to actual conditions. In some examples, the raw materials for forming the polyurethane may contain 3-8 parts by weight of anti-UV nanofiller, 3-8 parts by weight of hydrophobically modified isocyanate, 0.1-0.3 parts by weight of dispersant, 30-40 parts by weight of ordinary filler, 5-10 parts by weight of weather-resistant filler, 5-15 parts by weight of plasticizer, 0.1-0.3 parts by weight of defoamer, 0.05-0.1 parts by weight of accelerator, 0.05-0.1 parts by weight of amine catalyst, 15-25 parts by weight of polyether polyol, 1-5 parts by weight of aspartic acid ester internal plasticizing latent amine, and additionally 5-15 parts by weight of aliphatic isocyanate.
[0054] In general, the polyurethanes proposed in the present disclosure may have at least one of the following advantages:
[0055] 1) Excellent weather resistance, can withstand 2500 hours of artificial weathering. It has excellent weather resistance and is particularly suitable for waterproofing, decoration, and protection of concrete and color-coated steel surfaces on outdoor non-walkable roofs.
[0056] 2) Outstanding self-cleaning effect. The contact angle reaches 150°, which can achieve a lotus leaf effect, achieving the effect of being cleaned by rainwater, and the duration period is long, reaching more than 5 years.
[0057] 3) Excellent sunlight reflection ability. The hemispherical reflectivity of sunlight reaches over 80%, which can reduce the surface temperature of the coating and improve the energy efficiency of the building.
[0058] In another aspect of the present disclosure, a method for preparing the aforementioned polyurethane is provided, comprising the steps of forming a hydrophobically modified isocyanate, mixing the hydrophobically modified isocyanate, a polyether polyol, and an additive for prepolymerization, and then adding a latent amine to obtain the polyurethane.
[0059] In some examples, forming the hydrophobically modified isocyanate includes: adding a solution containing an anti-UV nanofiller and a low surface energy component to the isocyanate, and stirring the reaction in an oil bath at 80-120 degrees Celsius, wherein the solution containing the anti-UV nanofiller contains aspartic acid ester-type hindered secondary amine.
[0060] In some examples, obtaining the solution containing the anti-UV nanofiller comprises the following steps: adding a solvent to the aspartic acid ester hindered secondary amine, wherein the anti-UV nanofiller is dispersed in the solvent, and heating and stirring the reaction for 12-24 hours.
[0061] In some examples, the latent amine is an internal plasticizing latent amine, and the formation of the internal plasticizing latent amine includes: adding aspartic acid ester hindered secondary amine to a closed reactor, and adding a solvent; adding benzaldehyde dropwise under stirring conditions, controlling the reaction temperature to be no higher than 80°C, and continuing to keep the reaction warm after the addition is completed; refluxing the reacted material to remove water, and performing reduced pressure distillation treatment.
[0062] In a specific example of the present disclosure, the method may include the following steps:
[0063] 1. Preparation of UV-resistant nanofiller solution: First, disperse the nanoparticles in a solvent at a ratio of 8 wt%. Add an equal amount of solvent to the aspartic acid ester-type hindered secondary amine. The solvent can be added to the aspartic acid ester solution by constant pressure titration. Stir continuously at below 40°C for 12-24 hours to obtain the solution. The solvent used in this step is not particularly limited, as long as it can fully disperse the above components.
[0064] 2. Preparation of superhydrophobic modified isocyanate: Add the above anti-UV nanofiller solution and low surface energy small molecule material (such as fluorosilane) to isocyanate, place it in an oil bath at 80-120°C, stir and react for 10-15 hours, and then cool it down for use.
[0065] 3. Preparation of latent plasticizing amine in aspartic acid ester: Aspartic acid ester having the structure of formula (I) is pumped into a reaction kettle and cyclohexane is added. Benzaldehyde is added dropwise with stirring, and the temperature is controlled to be no higher than 80°C. After the addition is complete, the reaction is continued at this temperature for 0.5-2 hours, and then the temperature is raised to reflux to remove the water. After the water removal is complete, the solution is cooled to room temperature and the fraction above 130°C is collected by vacuum distillation.
[0066] 4. Preparation of polyurethane: Add the super-hydrophobic isocyanate grafted and modified in step 2, ordinary filler and weather-resistant filler (pre-dried to less than 0.05% moisture), plasticizer, dispersant, defoamer, polyol (tested moisture content less than 0.05%), etc. to a reactor, and add the modified nano-light-control material in step 1. Stir and react at 60°C for 2-4 hours, then raise the temperature to not less than 80°C and add aliphatic isocyanate. React for 3-5 hours, then measure the NCO content of the prepolymer. After reaching the set value, add the latent amine in step 3 dropwise, stir, add accelerator and amine catalyst, and test the fineness to reach microns.
[0067] In another aspect of the present disclosure, a coating is provided, wherein the coating comprises polyurethane, and the polyurethane is as described above or prepared by the method described above.
[0068] In some examples, the coating satisfies at least one of the following conditions: the solid content of the coating is not less than 80%; the film layer formed by the coating has a water contact angle of not less than 120 degrees; the artificial weathering time of the film layer formed by the coating is not less than 2000 hours; the solar hemispherical reflectivity of the film layer formed by the coating is not less than 80%.
[0069] The coating has all the features and advantages described above for polyurethane, which will not be repeated here. In some examples, the coating may have the properties shown in Table 1 below:
[0070] Table 1
[0071]
[0072] The methods used in the following examples are conventional methods unless otherwise specified, and the reagents used are commercially available reagents unless otherwise specified. HMDI and IPDI were purchased from Wanhua, respectively; polyether polyol 2000D, polyether polyol 1000D, and polyether polyol N330 were purchased from Wanhua, respectively; common fillers 101a heavy calcium and talc were both purchased from Jiangsu Qunxin; weather-resistant filler titanium dioxide 960 was purchased from DuPont, and barium sulfate 051 was purchased from Qunxin (titanium dioxide: barium sulfate = 2:1); plasticizer chlorinated paraffin No. 52 environmentally friendly was purchased from Oriental Dragon, and chloropalm oil methyl ester environmentally friendly was purchased from Luoyang Sanjin (the ratio of the two was 1:1); light-control nanomaterials titanium oxide, tungsten oxide, cerium oxide, and vanadium oxide were purchased from the Institute of Organic Chemistry of the Yangtze River Delta Innovation Center, and solvent oil No. 150 was purchased from Jiangsu Hualun; the defoamer was BYK Chemical 066N, the dispersant was Wuhan University silicone WD50, the accelerator was sublimed pure salicylic acid, and the amine catalyst was purchased from BASF DMDEE.
[0073] Example 1 Preparation of Super Weather-Resistant Polyurethane Self-Cleaning Reflective Coating
[0074] The raw materials include: 7 parts of HMDI, 10 parts of polyether 2000, 5 parts of polyether 1000, 10 parts of polyether 330N, 5 parts of light-controlled nano solution, 5 parts of super-hydrophobic modified isocyanate, 10 parts of plasticizer, 1.2 parts of aspartic acid ester internal plasticizing latent amine, 36.02 parts of ordinary filler (heavy calcium: talc = 2:1), 10 parts of weather-resistant filler (titanium dioxide: barium sulfate = 2:1), 0.3 parts of dispersant, 0.3 parts of defoaming agent, 0.1 parts of accelerator, and 0.08 parts of amine catalyst (all the above are parts by weight or mass ratio).
[0075] The preparation method includes: adding grafted modified super-hydrophobic isocyanate, filler (pre-dried to less than 0.05% moisture), dispersant, defoamer, plasticizer (dehydrated to less than 0.05%), and polyol (tested moisture content is less than 0.05%) into a reactor, and adding the modified nano-light-controlled solution, stirring and reacting at 60°C for 3 hours, then heating to 80°C and adding aliphatic isocyanate, reacting for 4 hours, and then measuring the NCO content of the prepolymer. After reaching the set value, latent amine is added dropwise, stirred for 1 hour, adding accelerator and amine catalyst, stirring and degassing at -0.095MPa and 60°C for 30 minutes, and then the single-component polyurethane coating can be obtained.
[0076] Example 2 Preparation of Super Weather-Resistant Polyurethane Self-Cleaning Reflective Coating
[0077] The raw materials include: 7 parts of HMDI, 10 parts of polyether 2000, 26 parts of polyether 330N, 5 parts of light-controlled nano solution, 5 parts of super-hydrophobic modified isocyanate, 10 parts of plasticizer, 1.2 parts of aspartic acid ester internal plasticizing latent amine, 32.02 parts of ordinary filler (heavy calcium: talc = 2:1), 10 parts of weather-resistant filler (titanium dioxide: barium sulfate = 2:1), 0.3 parts of dispersant, 0.3 parts of defoaming agent, 0.1 parts of accelerator, and 0.08 parts of amine catalyst (all the above are parts by weight or mass ratio).
[0078] The preparation method includes the following steps: adding grafted modified super-hydrophobic isocyanate, filler (pre-dried to below 0.05% moisture), dispersant, defoamer, plasticizer (dehydrated to below 0.05%), and polyol (tested moisture content below 0.05%) into a reactor, and adding the modified nano-light-controlled solution, stirring and reacting at 60°C for 3 hours, then heating to 80°C and adding aliphatic isocyanate, reacting for 4 hours, and then measuring the NCO content of the prepolymer. After reaching the set value, latent amine is added dropwise, stirred for 1 hour, adding accelerator and amine catalyst, stirring and degassing at -0.095MPa and 60°C for 30 minutes, and then the single-component polyurethane coating can be obtained.
[0079] Example 3 Preparation of Super Weather-Resistant Polyurethane Self-Cleaning Reflective Coating
[0080] The raw materials include: 10 parts of IPDI, 20 parts of polyether 2000, 10 parts of polyether 1000, 3 parts of light-controlled nano solution, 3 parts of super-hydrophobic modified isocyanate, 10 parts of plasticizer, 1.2 parts of aspartic acid ester internal plasticizing latent amine, 32.02 parts of ordinary filler (heavy calcium: talc = 2:1), 10 parts of weather-resistant filler (titanium dioxide: barium sulfate = 2:1), 0.3 parts of dispersant, 0.3 parts of defoaming agent, 0.1 parts of accelerator, and 0.08 parts of amine catalyst (all the above are parts by weight or mass ratio).
[0081] The preparation method includes the following steps: adding grafted modified super-hydrophobic isocyanate, filler (pre-dried to below 0.05% moisture), dispersant, defoamer, plasticizer (dehydrated to below 0.05%), and polyol (tested moisture content below 0.05%) into a reactor, and adding the modified nano-light-controlled solution, stirring and reacting at 60°C for 3 hours, then heating to 80°C and adding aliphatic isocyanate, reacting for 4 hours, and then measuring the NCO content of the prepolymer. After reaching the set value, latent amine is added dropwise, stirred for 1 hour, adding accelerator and amine catalyst, stirring and degassing at -0.095MPa and 60°C for 30 minutes, and then the single-component polyurethane coating can be obtained.
[0082] Comparative Example 1
[0083] The remaining operations are the same as those in Example 1, with the only difference being that the light-controlled nano-solution is not added and the amounts of other materials added are adaptively adjusted.
[0084] Comparative Example 2
[0085] The remaining operations were the same as those in Example 1, except that the super-hydrophobic modified isocyanate was not added, and the amounts of other materials added were adjusted adaptively.
[0086] Comparative Example 3
[0087] The remaining operations are the same as those in Example 1, except that the internal plasticizing latent amine is not added and the amounts of other materials added are adjusted adaptively.
[0088] Performance Testing
[0089] The waterproof coatings prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the following performance tests. The specific results are shown in Table 2:
[0090] Table 2
[0091]
[0092]
[0093] As can be seen from Table 2 above, the coatings of the embodiments of the present disclosure all have good performance, high weather resistance, large light reflectivity and water contact angle, and can meet the artificial weathering standard of more than 2500h.
[0094] In the description of this specification, it should be understood that the terms "center", "thickness", "up", "down", "front", "back", "horizontal", "top", "bottom", "inside", "outside", "axial", "radial", "circumferential" and the like to indicate directions or positions are only for the convenience of describing the present disclosure and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as a limitation on the present disclosure.
[0095] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features being referred to. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of such features. Throughout the present disclosure, "plurality" means two or more, unless otherwise specifically defined.
[0096] In this disclosure, unless otherwise expressly specified or limited, terms such as "mounted," "connected," "connect," and "fixed" should be understood broadly. For example, they may refer to fixed connections, detachable connections, or integration; mechanical connections, electrical connections, or communication; direct connections or indirect connections through an intermediate medium; and internal connections between two components or interactions between two components. Those skilled in the art will understand the specific meanings of these terms in this disclosure based on specific circumstances.
[0097] In the present disclosure, unless otherwise expressly specified or limited, a first feature being "above" or "below" a second feature may include the first and second features being in direct contact, or may include the first and second features being in contact not directly but through another feature between them. Moreover, a first feature being "above," "above," and "above" a second feature includes the first feature being directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below," "below," and "below" a second feature includes the first feature being directly above and obliquely above the second feature, or simply indicates that the first feature is lower in level than the second feature.
[0098] The disclosure above provides many different embodiments or examples for implementing different structures of the present disclosure. In order to simplify the present disclosure, the components and settings of specific examples are described above. Of course, these are merely examples and are not intended to limit the present disclosure. In addition, the present disclosure may repeat reference numbers and / or reference letters in different examples. Such repetition is for the purpose of simplicity and clarity and does not in itself indicate the relationship between the various embodiments and / or settings discussed.
[0099] The above are only specific embodiments of the present disclosure, but the scope of protection of the present disclosure is not limited thereto. Any person skilled in the art can easily conceive of various modifications or substitutions within the technical scope disclosed in this disclosure, and such modifications or substitutions should be included in the scope of protection of the present disclosure. Therefore, the scope of protection of the present disclosure should be based on the scope of protection of the claims.
Claims
1. A polyurethane, characterized in that The raw materials for forming the polyurethane include: UV-resistant nanofillers; Hydrophobically modified isocyanates; Polyether polyols; Latent amines; and additive, The hydrophobically modified isocyanate is formed by grafting and modifying a low surface energy component in the presence of aspartic acid ester sterically hindered secondary amine.
2. The polyurethane according to claim 1, characterized in that The viscosity of the polyurethane is 6000-9000 mPa.s.
3. The polyurethane according to claim 1, characterized in that The anti-UV nanofiller and the latent amine are modified by the aspartic acid ester sterically hindered secondary amine.
4. The polyurethane according to any one of claims 1 to 3, characterized in that The aspartic acid ester hindered secondary amine is a compound shown in Formula I: Wherein, R1-R4 are independently selected from C1-C8 alkyl groups.
5. The polyurethane according to claim 4, characterized in that R1-R4 are each independently a C2-C8 straight-chain alkyl group.
6. The polyurethane according to claim 1, characterized in that The anti-UV nano filler includes at least one of titanium dioxide, cerium oxide, zinc oxide, tungsten oxide, silicon oxide and vanadium oxide, The particle size of the anti-UV nano material is 20-100 nm.
7. The polyurethane according to claim 1, characterized in that The additive includes at least one of a dispersant, a defoamer, a filler, a plasticizer, and a promoter.
8. A method for preparing the polyurethane according to any one of claims 1 to 7, characterized in that: The method comprises the steps of forming a hydrophobically modified isocyanate, mixing the hydrophobically modified isocyanate, a polyether polyol and an additive for prepolymerization, and then adding a latent amine to obtain the polyurethane.
9. The method according to claim 8, characterized in that The hydrophobically modified isocyanate is formed by adding a solution containing an anti-UV nanofiller and a low surface energy component to the isocyanate, and stirring the mixture in an oil bath at 80-120 degrees Celsius for reaction. The solution containing the anti-UV nanofiller contains aspartic acid ester-type hindered secondary amine.
10. The method according to claim 9, characterized in that The preparation of the solution containing the anti-UV nanofiller comprises the following steps: A solvent is added to the aspartic acid ester hindered secondary amine, wherein the anti-UV nano filler is dispersed in the solvent, and the mixture is heated and stirred to react for 12-24 hours.
11. The method according to claim 8, characterized in that The latent amine is an internal plasticizing latent amine, and the formation of the internal plasticizing latent amine comprises: Adding aspartic acid ester hindered secondary amine into a closed reactor, and adding a solvent; Add benzaldehyde dropwise under stirring, control the reaction temperature not higher than 80°C, and continue to keep the temperature for reaction after the addition is completed; The reacted material is refluxed to remove water and subjected to reduced pressure distillation.
12. A coating, characterized in that: The coating comprises polyurethane, and the polyurethane is as described in any one of claims 1-7, or is prepared by the method described in any one of claims 8-11.
13. The coating according to claim 12, characterized in that The coating satisfies at least one of the following conditions: The solid content of the coating is not less than 80%; The film layer formed by the coating has a water contact angle of not less than 120 degrees; The artificial weathering time of the film layer formed by the coating is not less than 2000 hours; The solar hemispherical reflectivity of the film layer formed by the coating is not less than 80%.